Effect of radiation processing on phenolic antioxidants in cereal and legume seeds: A review. (1st December 2022) - Shi, Zhiqiang; Liu, Ying; Hu, Zhiming; Liu, Liu; Yan, Qinghai; Geng, Dandan; Wei, Min; Wan, Yan; Fan, Gaoqiong; Yang, Hongkun; Yang, Pinghua
Highlights: Radiation processing improves phenolic compounds in cereal and legume seeds. Radiation processing enhances antioxidant activities in cereal and legume seeds. Radiation processing induces the transformation of phenolic compounds in cereal and legume seeds. Radiation processing causes the breakage of the glycosidic bonds of phenolic compounds with carbohydrates. Possible mechanisms of the effect of radiation processing on phenolic compounds in cereal and legume seeds are proposed. Abstract: Phenolic compounds in cereal and legume seeds show numerous benefits to human health mainly because of their good antioxidant capacity. However, long-term storage and some improper preservation may reduce their antioxidant potential. It is necessary to retain or modify the phenolic antioxidants with improved technology before consumption. Radiation processing is usually applied as a physical method to extend the shelf life and retain the quality of plant produce. However, the effect of radiation processing on phenolic antioxidants in cereal and legume seeds is still not well understood. This review summarizes recent research on the effect of radiation, including ionizing and nonionizing radiation on the content and profile of phenolic compounds, and antioxidant activities in cereal and legume seeds, the influencing factors and possible mechanisms are also discussed. The article will improve the understanding of radiation effect on phenolic antioxidants, and promote the radiation modification of natural phenolic compounds in cereal and legume seeds and other sources.